Investigation on the microstructure evolution and deformation behavior of Mg–2Zn-0.5Mn-0.2Ca-xNd/yLa alloy by in-situ tensile - Jie Mi; Shengquan Liang; Shiyu Luan; Qianlong Ren; Xin Che; Peipeng Jin (Journal of Materials Research and Technology)
Multi-microalloying rare earth elements are expected to improve the properties of magnesium alloys. In this study, Mg–2Zn-0.5Mn-0.2Ca-0.3Nd-0.7La (alloy A) and Mg–2Zn-0.5Mn-0.2Ca-0.7Nd-0.3La (alloy B) alloys with microalloying Nd and La were developed. Compared with alloy B, the tensile load of alloy A is higher and the plasticity is lower. The microstructure evolution and deformation behavior analyzed by in-situ SEM and EBSD show that the basal texture intensity of alloy A is larger, which promotes more prismatic slip during the tensile process, resulting in higher tensile load, while alloy B with higher Nd content produces more pyramidal slip in the later stage of deformation, which contributes to higher plasticity. The Nd–Zn phase, Mg–Zn phase and Mg–Mn phase are mainly formed in the two alloys. The alloy B with higher Nd content precipitates more Nd–Zn phase. The Nd–Zn phase rich in Zn layer promote dislocation transfer and improve the plasticity of alloy B, while more Mg–Zn phase and Mg–Mn phase in alloy A pin dislocations and improve strength. In addition, tensile twins are produced during the tensile of the two alloys and the content is similar, but the extremely low twin content makes its effect on the mechanical properties of the two alloys negligible. Therefore, the difference in mechanical properties of the two alloys is mainly related to the texture intensity and the content of the second phase precipitated by different additions of rare earth elements.